2018
DOI: 10.14739/2310-1210.2018.4.135589
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum 48 kDa form of unconventional myosin 1c characterizes the early stage of multiple sclerosis

Abstract: В соответствии с современными представлениями о рассеянном склерозе (РС), значительную роль в развитии патологического процесса играют B-лимфоциты. В связи с этим имеет значение поиск новых биомаркеров В-лимфоцитарного происхождения, которые могут отражать клинические особенности этого заболевания. Цель работы-оценить соотношение между уровнем 48 кДа формы неконвенционного миозина 1с (48 кДа Myo 1c) в сыворотке крови больных рассеянным склерозом и стадией этого заболевания, его тяжестью и типом течения.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The accumulated data convincingly demonstrate that 48 kDa polypeptide is a short form of unconvential myosin 1c earlier found by us in blood serum of patients with autoimmune and hematoncological disease [11,12]. It is known that Myo1C (molecular mass 121.7 kDa) is abundantly expressed in mammalian B lymphocytes [12] and the level of 48 kDa fragment in blood serum could be tightly associated with blood cells degradation [11,12,17]. Further investigation demonstrated that 48 kDa myosin 1C capable of binding in blood serum with IgG and IgM immunoglobulins [18], as well as with component 3 of the complement and the antithrombin-III [19].…”
Section: Resultsmentioning
confidence: 62%
“…The accumulated data convincingly demonstrate that 48 kDa polypeptide is a short form of unconvential myosin 1c earlier found by us in blood serum of patients with autoimmune and hematoncological disease [11,12]. It is known that Myo1C (molecular mass 121.7 kDa) is abundantly expressed in mammalian B lymphocytes [12] and the level of 48 kDa fragment in blood serum could be tightly associated with blood cells degradation [11,12,17]. Further investigation demonstrated that 48 kDa myosin 1C capable of binding in blood serum with IgG and IgM immunoglobulins [18], as well as with component 3 of the complement and the antithrombin-III [19].…”
Section: Resultsmentioning
confidence: 62%
“…Indirectly, our hypothesis about the existence of the “acute” and “steady” phases in time dynamics of the 48/Myo1C content in blood serum of the autoimmune patients, including Covid-19 patients, is in agreement with the results of our recent clinical investigation of the correlation between the level of the 48/Myo 1C in blood serum of the multiple sclerosis (MS) patients and the clinical status of this disease. We have demonstrated that higher level of the 48/Myo1C in blood serum of the MS patients was associated with an early stage of this autoimmune disease characterized by its short duration and the relapsing-remitting type ( Nehrych et al, 2018 ). By the way, the exacerbations of the disease in the MS patients were cured with the dexamethasone ( Berkovich, 2013 ).…”
Section: Resultsmentioning
confidence: 94%
“…There is no reliable information regarding the biological functions of a 48 kDa fragment of the unconventional myosin 1C. Its role as a diagnostic and prognostic biomarker of the severity of the disease was shown in the multiple sclerosis patients ( Nehrych et al, 2018 ). Here, we prepared primary culture of the anti-CD3 antibody-activated lymphocytes of the peripheral blood of healthy human and treated these cells with the 48/Myo1C.…”
Section: Resultsmentioning
confidence: 99%
“…non‐Hodgkin’s lymphoma; Kit et al, 2018; Myronovskij, Shalay, Spivak, Stoika, & Kit, 2017). The results of our clinical investigation of 48/Myo1C in blood serum of 60 multiple sclerosis patients vs. 20 healthy volunteers demonstrated a correlation of the amount of this protein with an early stage of multiple sclerosis, when the diagnosis of this disease is most complicated (Nehrych et al, 2017, 2018). Thus, we suggested that 48/Myo1C might be a potential diagnostic marker for estimation of the progression of some autoimmune, oncological and neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 92%